124k views
13 votes
Solve::::::::::::::::

\sf \: 3(y + 3) - 10 = 2y + 1


User Medena
by
4.7k points

1 Answer

3 votes

Solution:

3(y + 3) - 10 = 2y + 1

  • Let us first multiply 3 and (y + 3).

or, 3y + 9 - 10 = 2y + 1

  • Now, transpose the value of 2y to the left hand side and 9 and -10 to the right hand side.

or, 3y - 2y = 1 - 9 + 10

  • Do the addition and subtraction.

or, y = 2

  • So, we have got the value of y.

Verification:

LHS

= 3 (2 + 3) - 10

= 3 (5) - 10

= 15 - 10

= 5

RHS

= 2 (2) + 1

= 4 + 1

= 5

So, LHS = RHS [verified]

Answer:

y = 2

Hope you could understand.

If you have any query, feel free to ask.

User Drinking
by
5.0k points